The association of tissue doppler E/e' ratio with poor survival is modified by gender and is attenuated with advanced age. (14th October 2021) - Wasserstrum, Y; Gilead, R; Kuperstein, R; Ben-Zekry, S; Vatury, O; Mazor-Dray, E; Hai, I; Segev, A; Klempfner, R; Feinberg, M; Maor, E
Abstract: Introduction: Contemporary guidelines recommend a universal cutoff of 14 for the ratio between early mitral flow wave and early diastolic mitral annulus velocity measured by tissue doppler (E/e' ratio). While age-dependent normal E/e' values have been suggested, outcome data is lacking. Purpose: We sought to evaluate the modification effect of age and gender on the prognostic value of the E/e' ratio. Methods: Consecutive patients who underwent echocardiographic evaluation between 2009 and 2021 (N=104, 315) in a single tertiary cardiovascular center. Patients with left or right ventricular dysfunction, any significant valvular disease, structural heart disease or evidence of pulmonary hypertension were excluded. Cancer and mortality data were available for all subjects from national registries. Patients with a metastatic malignancy at baseline or during follow up were excluded. Cox regression models were applied. Results: Overall, 44, 541 patients were included in the final analysis. Mean age was 55±17, 59% were male and 63% of the exams were performed in an outpatient setting. An elevated E/e' ratio above 14 was documented in 2, 598 (7%) patients. During a median follow-up of 5.7 (IQR 2.8–9.1) years, 5, 015 (11.3%) patients died. Kaplan Meier survival analysis demonstrated that the cumulative probability of death at 6 years was 23.4% (21.6–25.3) among patients with elevated E/e' ratio compared with 9.7% (9.3–10.0) among patients with E/e'<14 (p Log rank <0.001). This difference was less significant as age progressed (figure 1). Multivariate cox-regression model yielded consistent results such that an elevated E/e' ratio was associated with 2.66-fold increased risk of death during follow up (95% CI 2.44–2.89, p<0.001), and there was a decline in the increased risk and significant as age advanced in both genders (figure 2). Interaction analysis was significant for both gender and age such the association of elevated E/e' ratio with poor survival was more significant among men compared with women and among young vs. older subjects. Among women, elevated E/e' was associated with 2.4-fold increased risk of death versus 2.7-fold increased risk among men. Similarly, the hazard ratio for death associated with elevated E/e' was 2.29 (95% CI 1.74–3.02), 1.8 (95% CI 1.5–2.1), 1.13 (95% CI 0.97–1.31) and 1.07 (95% CI 0.92–1.25) for the age groups of <60, 60–70, 70–80 and >80, respectively. In a sensitivity analysis, similar findings were seen in when excluding patients with mild hypertrophy (maximal wall thickness >12mm) and without any mitral annulus calcification. Conclusion: In apparently normal hearts, an elevated E/e' ratio is independently associated with increased mortality. This association is more pronounced among men and is attenuated with increased age. This study supports the need for gender-specific and age-specified outcome data with respect to measures of diastolic dysfunction. Funding Acknowledgement: Type of funding sources: None.